2022
DOI: 10.3389/fmed.2022.814810
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Observation of Higher-Order Aberrations and Microdistortions in Bowman’s Layer After Small Incision Lenticule Extraction for the Correcting Myopia With Spherical Equivalent Higher Than −9.0 Diopters

Abstract: PurposeTo evaluate the outcomes in corneal higher-order aberrations (HOAs) and microdistortions in the Bowman’s layer after femtosecond laser small incision lenticule extraction (SMILE) for correcting extremely high myopia.MethodsThis prospective study included patients with myopia with spherical equivalent ≥ -9.0 Diopters (D). SMILE was performed in forty eyes of 40 patients. Pentacam was used to evaluate HOAs before and at 1 day, 3 months, 6 months, and 2 years after surgery. Fourier-domain optical coherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This finding is supported by Chen X et al [10], who reported higher vertical coma after SMILE versus wavefront-guided femtosecond LASIK. These differences might be associated with SMILE's unique centration technique, which employs the corneal vertex as a reference point, diverging from the pupillary center used in LASIK and PRK, aligning with findings from the existing literature [6,[10][11][12][13][14]. In LASIK and PRK, variations in pupil size relative to treatment zones result in distinct HOA inductions.…”
Section: Discussionmentioning
confidence: 60%
“…This finding is supported by Chen X et al [10], who reported higher vertical coma after SMILE versus wavefront-guided femtosecond LASIK. These differences might be associated with SMILE's unique centration technique, which employs the corneal vertex as a reference point, diverging from the pupillary center used in LASIK and PRK, aligning with findings from the existing literature [6,[10][11][12][13][14]. In LASIK and PRK, variations in pupil size relative to treatment zones result in distinct HOA inductions.…”
Section: Discussionmentioning
confidence: 60%